2017
DOI: 10.1210/js.2017-00156
|View full text |Cite
|
Sign up to set email alerts
|

Somatic VHL Mutation in a Patient With MEN1-Associated Metastatic Pancreatic Neuroendocrine Tumor Responding to Sunitinib Treatment: A Case Report

Abstract: Multiple endocrine neoplasia type 1 (MEN1) and von Hippel-Lindau (VHL) are autosomal-dominant diseases caused by germline mutations in tumor-suppressor genes. A patient with a germline MEN1 mutation and a somatic VHL mutation in the tumor has not been reported. Herein, we report on a patient with MEN1 and a metastatic nonfunctioning pancreatic neuroendocrine tumor (PNET) with a somatic VHL mutation. This patient underwent a pancreaticoduodenectomy for a grade 2 PNET obstructing her pancreatic duct. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A VHL -associated CCRCC case in which a deletion of c.530-536 resulted in an Arg177Thr change has also been reported[ 23 ]. In addition, one study reported a rare VHL somatic c.529A>T mutation in a MEN1-associated metastatic pancreatic neuroendocrine tumor[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A VHL -associated CCRCC case in which a deletion of c.530-536 resulted in an Arg177Thr change has also been reported[ 23 ]. In addition, one study reported a rare VHL somatic c.529A>T mutation in a MEN1-associated metastatic pancreatic neuroendocrine tumor[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current setting where there are not much treatment methods available and high-level evidence-based research is difficult to achieve, our study is a very worthwhile approach. Of course, it is worthy of recommendation if we can identify the degree of angiogenesis by immunohistochemistry before treatment or whether gene sequencing can determine the associated VHL gene and other genes for individualized precise treatment 22…”
Section: Discussionmentioning
confidence: 99%
“…In one MEN1-related PanNET (WHO grade 2), a high methylation percentage of the VHL promoter was found together with loss of VHL protein expression. It has been reported that somatic VHL mutations and LOH of chromosomal locus 3p (with the site of VHL) may be involved in PanNET development and/or progression in MEN1 (38,39). DNA promoter hypermethylation of VHL has previously been described in 6% of sporadic PanNETs (40).…”
Section: Discussionmentioning
confidence: 99%